Fly Ash Innovation in Sustainable Agriculture: A Case Study of the INNDESA CSR Program by PT PLN Indonesia Power UBP Central Java 2 Adipala - Imam Siswo Utomo; Taufik Hidayanto; Adinda Aulia Nur Afifah; Ayu Widyanigrum (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This study aims to explore the innovative use of fly ash by PT PLN Indonesia Power UBP Central Java 2 Adipala as a natural insecticide within the INNDESA program. This is crucial as global climate change has brought food security issues to the forefront of strategic agendas for many countries, including Indonesia. Employing a qualitative case study approach, this research collected data through in-depth interviews with beneficiaries of the INNDESA program, supported by secondary data from relevant journals, mass media, program reports, and other supporting documents. The findings reveal that: (1) the utilization of fly ash in INNDESA innovation effectively replaces chemical pesticides by killing pests through abrasive mechanisms and preventing them from attacking crops, (2) the INNDESA program fosters economic improvement in communities through a circular economy system, and (3) the INNDESA program aims to establish sustainable, community-based food security as reflected in the establishment of the INNDESA Integration Forum.